The use of calcium hydroxide for the reduction of cervical dentin hypersensitivity - Ong, Catherine C.; Pangan, Maricel C.
Calcium hydroxide is widely used in dentistry. It is a common ingredient in cavity bases, liners and is used as an intracanal medicament. However studies have shown that it can also be used as a desensitizing agent on hypersensitive exposed dentin. The aim of this study is to evaluate the effectiveness of calcium hydroxide on the reduction of cervical dentin hypersensitivity and to compare its effects before, immediately after and 1 week after application. Nine patients with a total of 39 teeth were tested. To be eligible for inclusion, the teeth should have no carious lesions, no restorations nor excessive mobility. Calcium hydroxide liner catalyst was applied using a calcium hydroxide applicator and was allowed to remain on the affected surface for 5 minutes. Before and 1 minute after the treatment, each tooth was tested clinically using explorer and air blast and the patient asked to rate the degree of pain. Tests were repeated after 1 week.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Calcium hydroxide